Investigation on the mechanism of improving the forming quality of cavitation water jet micro-punching by using a rubber membrane - Li, Fuzhu; Meng, Wei; Mori, Stefano; Wang, Yun; Wang, Chunju; Guo, Yuqin (Springer, 2025)
Cavitation water jet micro-punching (CWJP) is a high-strain-rate micro-punching technique that utilizes high-energy shock waves generated by the collapse of cavitation bubbles to perform micro-punching on metal foils. However, defects such as brittle fracture, warpage deformation, and edge tearing often occur in the micro-punched holes due to the reverse impact of high-speed backflow. To solve this issue, a novel rubber membrane-assisted cavitation water jet micro-punching (RA-CWJP) technique was proposed in the present work, in which a flexible rubber membrane was introduced as a soft punch to prevent cavitation water jet from entering the die hole. Comparative experiments of the CWJP and RA-CWJP processes were conducted on 50 μm-thick T2 copper foils. The forming quality of micro-punched holes in both processes was evaluated based on microscopic morphology (fracture surface and cross section), shape, and dimensional accuracy. Additionally, the effect of high-speed backflow on the CWJP process was analyzed in detail. Fluid–solid coupling numerical simulations were conducted to better understand the improvement mechanism of the rubber membrane on the forming quality of micro-punched holes. The research results show that applying a 200 μm-thick rubber membrane to the CWJP process prevents brittle fractures, warpage, and edge tearing caused by the reverse impact force of backflow. Meanwhile, the rubber membrane also increases the depth of the shearing zone, and reduces both the rollover zone and burr formation. Compared to the CWJP process, the shape and dimensional accuracy of micro-punched holes formed by the RA-CWJP process increased by 16.1%–63.5% and 45.4%–82.2%, respectively. In the RA-CWJP process, the excellent fluidity and compressibility of the rubber membrane enable precise shearing separation of the copper foil along the die edge. Furthermore, the rubber membrane reduces elastic recovery after punching through enhanced plastic deformation, significantly improving the dimensional accuracy.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 4016 Materials engineering; 4017 Mechanical engineering; Rubber membrane; Cavitation water jet; Metal foil; Micro-punching; Forming quality